Enhanced catalytic activity of new di-site onium salt in the kinetics of α-Tolunitrile monoalkylation. (2021) - Vivekanand, P.A.; Fayaz, T.K.; Harikumar, S.; Kamaraj, P.; Thiruvengadam, V.; Shanmugam, V.
Abstract: In this study, we investigate in detail the catalytic efficiency of 1, 4-bis-(ethylmethyleneammounium chloride)-2, 5- dimethoxy benzene, BEMACDB (multi-site phase transfer catalyst) by observing the pseudo-first order kinetics of mono-alkylation of α-Tolunitrile (ATN). The formation of product was monitored by GC. The comparative study of catalytic efficiency of the new catalysts with single-site salts reveals higher catalytic activity for new catalysts under varying experimental conditions ([BEMACDB], [Base], [ATN], Stirring Speed and Temperature). By understanding the kinetics of mono-alkyaltion, we further establish the experimental parameters that influence reaction conditions. With the support of kinetic data we establish the suitable mechanism for monoalklation of ATN. The catalyst shows consistent catalytic activity in the C-alkylation of ATN in different experimental conditions.